Changes in Corneal Detection Thresholds After Repeated Tear Film Instability - Awisi-Gyau, Deborah; Begley, Carolyn G.; Situ, Ping; Simpson, Trefford L. (Investigative ophthalmology & visual science, 2019)
To use a human-based model to study the effects of repeated tear film instability on corneal detection thresholds to cold, mechanical, and chemical stimuli. Twenty-five subjects participated in three study visits. A computer-controlled Belmonte esthesiometer was used to estimate corneal detection thresholds to cold, mechanical, and chemical stimuli before, after, and 30 minutes following 10 consecutive sustained tear exposure (STARE) trials. Subjects turned a pain knob (0-10) to indicate discomfort during STARE trials. The area of tear breakup and thinning in each trial was analyzed. Symptoms were evaluated by the Current Symptom Questionnaire (CSQ). There was a significant time effect on CSQ symptoms during both visits (Friedman test, P < 0.001), with immediately after repeated STARE and 30 minutes later significantly differing from before STARE (Wilcoxon, P < 0.017). Tear breakup occurred in every trial, ranging from 25% to 88% of the exposed corneal area and all subjects indicated discomfort during trials. There was a significant time effect on mechanical thresholds between before STARE mechanical thresholds and 30 minutes later (repeated measures analysis of variance [ANOVA] P < 0.001), but not cold (P = 0.057) or chemical (P = 0. 565) thresholds. In this study, tear breakup during STARE trials was associated with discomfort, which when repeated, resulted in increased symptoms of ocular discomfort and alterations of mechanical sensory thresholds after 30 minutes. These results suggest that tear film instability, which is thought to occur repeatedly during normal blinking among dry eye patients over the day, can produce neurosensory alterations.